English as a lingua franca in Thailand: a case study of English used on signs in tourist domains - Ngampramuan, Wipapan (2016)
English has been used around Thailand for wider communication between Thai and non-Thai speakers. This thesis focuses on the use of English for communication on signs in tourist domains across Thailand. The research aims to, first, analyse the main characteristics of English used in Thailand, so-called Thai English, and, second, find out to what extent Thai English is intelligible to non-Thai speakers. The study was drawn from 1,828 photos of Thai English signs. The signs were first categorised based on grammatical features and lexico-semantic features. Then, 30 signs were selected to make an online questionnaire about the intelligibility of Thai English. They were divided into three levels, namely Level 1: no errors (but socio-culturally unintelligible), Level 2: minor errors, and Level 3: major errors. The questionnaire was done by 456 international and 810 Thai participants. Then 51 in-depth interviews were conducted. The findings showed that signs with Thai English could be fairly understood when they contained no errors (Level 1) or minor errors (Level 2). However, when signs contained major errors (Level 3), neither native nor non-native speakers of English could understand the intended meanings. The key factors contributing to the intelligibility of Thai English were non/native English speaking background and English proficiency of the participants. The research found that native speakers could understand Thai English better than non-native speakers because the former could negotiate the meanings of the Thai English messages better than the latter. Non-native speakers with higher English proficiency could also understand Thai English better than those with lower English proficiency. Finally, the research found that international participants tended to pay more attention to meaning than to form. If they could grasp the meaning of the message, albeit grammatically incorrect, they would still consider the error not serious. Conversely, Thai participants appeared to be pedantic about grammar and would consider the items with grammatical errors more serious than those with lexico-semantic errors. Thai participants accepted that the research into Thai English helped to raise their awareness of using English in everyday life while international participants revealed that this research helped to make them understand the use of English as a lingua franca in Thailand better.